2015
DOI: 10.1523/jneurosci.0045-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Oxygen Sensitivity of Astrocytes

Abstract: In terrestrial mammals, the oxygen storage capacity of the CNS is limited, and neuronal function is rapidly impaired if oxygen supply is interrupted even for a short period of time. However, oxygen tension monitored by the peripheral (arterial) chemoreceptors is not sensitive to regional CNS differences in partial pressure of oxygen (P O 2 ) that reflect variable levels of neuronal activity or local tissue hypoxia, pointing to the necessity of a functional brain oxygen sensor. This experimental animal (rats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
341
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(352 citation statements)
references
References 63 publications
8
341
0
3
Order By: Relevance
“…AAV8-DIO-GFAP-hM3Dq-mCherry (3 × 10 13 virus molecules/ml, 1.5 μl) was bilaterally injected into the medulla of Gfap-Cre mice. The medulla was located using stereotaxic coordinates: from the bregma -6.74 ± 0.1 mm caudal, 1.4 ± 0.1 mm lateral, and 5.7 mm ventral.…”
Section: Viral Expression Of Hm3dqmentioning
confidence: 99%
See 1 more Smart Citation
“…AAV8-DIO-GFAP-hM3Dq-mCherry (3 × 10 13 virus molecules/ml, 1.5 μl) was bilaterally injected into the medulla of Gfap-Cre mice. The medulla was located using stereotaxic coordinates: from the bregma -6.74 ± 0.1 mm caudal, 1.4 ± 0.1 mm lateral, and 5.7 mm ventral.…”
Section: Viral Expression Of Hm3dqmentioning
confidence: 99%
“…Although SNA is mainly considered a product of integration by neuronal networks, recent evidence suggests that Gq G protein-coupled receptor (Gq-GPCR) activation in glial fibrillary acidic protein-expressing (GFAP + ) glia (CNS astrocytes and non-myelinating peripheral glia) also contributes to homeostatic control of blood gases (11)(12)(13) and gastrointestinal motility (14,15) via modulation of local neuronal activity. Recently, we showed that selective activation of Gq-GPCR signaling in GFAP + glia in vivo led to acute changes in autonomic functions, including increases in heart rate and blood pressure (16).…”
Section: Introductionmentioning
confidence: 99%
“…Previously we found that even a short exposure of astrocytes to hypoxia results in an increase in intracellular calcium (Angelova et al, 2015). In the present study, a short episode of hypoxia induces the release of polyP by fusion of VNUT‐containing vesicles ( n  = 39, Figure 6f) suggesting that release of polyP from astrocytes may play a certain role in mediating the physiological response to brain hypoxia.…”
Section: Resultsmentioning
confidence: 90%
“…An Olympus total internal reflection fluorescence (TIRF) microscope was used to detect vesicular fusion events in astrocytes expressing VNUT–eGFP or CD63‐mKate, as described in detail previously (Angelova et al, 2015; Kasymov et al, 2013). Fluorescence was excited at 488 nm and collected at 500–530 nm for eGFP and excited at 488 nm and collected at 600–660 nm for mKate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation